Cross-relaxation of electronic excitation in lanthanide-doped crystals and glasses - Koren, Monika (Matrika, 2020)
Cross-relaxation due to dipole-dipole electrostatic interaction between electric dipole moments of lanthanide ions decreases the fluorescence quantum yield and shortens excited state lifetime. Despite that, cross-relaxation is important because it enables sensitized fluorescence, which is useful when emitting ions can't absorb the excitation light. Gain media is therefore co-doped with another type of lanthanide ions, which absorb the excitation light and transfer the electronic excitation to the ions, which produce fluorescence. This kind of gain media is used in solid-state lasers and optical fiber amplifiers.
Keywords: cross-relaxation; doping; dopiranje; electronic excitation; elektronska vzbuditev; fizika trdne snovi; križna relaksacija; lantanidi; lanthanides; solid state physics